Arthroscopic Management of Synovial Chondromatosis of the Ankle Joint: A Systematic Review of the Literature. Issue 9 (September 2020) - Al Farii, Humaid; Doyle-Kelly, Christopher; Marwan, Yousef; Volesky, Monika; Turcotte, Robert
Abstract : Background: Synovial chondromatosis (SC) of the ankle is a rare disorder in which metaplastic proliferation of synovia, tendon sheaths, and/or bursae leads to the formation of loose cartilaginous bodies within the joint space. While SC itself is a benign condition, its sequelae can be chronic and debilitating if left untreated, or if there is postoperative recurrence. Arthritic degeneration and malignant transformation to chondrosarcoma are among the more serious complications in the natural history of the disease; the latter occurs in approximately 5% of cases. We performed a systematic review of the literature on the arthroscopic management of ankle SC in order to better understand recurrence patterns and suggest an alternative approach to open arthrotomy. Methods: Using predetermined inclusion and exclusion criteria, the PubMed and Embase databases were searched for relevant articles related to arthroscopic surgical management of patients with confirmed SC of the ankle. Article selection and data abstraction were performed in 3 steps by 3 independent reviewers. Results: The initial search retrieved 116 articles, of which 15 were included. Those studies included 22 patients (14 to 63 years of age; 77% male) who were followed for a mean of 27 months (range, 8 weeks to 12 years) postoperatively. The cases represented a mix of primary and secondary SC etiologies, and almost entirely stage-III disease. Arthroscopic synovectomy with excision of loose bodies was a consistent feature of treatment, and bursectomy, debridement of osteochondral lesions or involved tendons, and osteophyte resection were performed as indicated. All but 1 case employed an anterior approach including anteromedial and anterolateral portals, and in several cases a 4-portal technique was used, which was subsequently proposed as a necessary approach for the definitive treatment of ankle SC. On the basis of the available data, complication and recurrence rates following arthroscopic management were very low. Conclusions: A growing pool of evidence is emerging to suggest favorable outcomes for arthroscopic treatment of SC of the ankle joint. However, more data on patient and surgical variables, as well as comparative studies with longer follow-up, are needed in order to draw definitive conclusions. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.